2020
DOI: 10.1103/physrevresearch.2.033367
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi liquid transport in the vicinity of the nematic quantum critical point of superconducting FeSe1xSx

Abstract: Non-Fermi liquids are strange metals whose physical properties deviate qualitatively from those of conventional metals due to strong quantum fluctuations. In this paper, we report transport measurements on the FeSe 1−x S x superconductor, which has a quantum critical point of a nematic order without accompanying antiferromagnetism. We find that in addition to a linear-in-temperature resistivity ρ xx ∝ T , which is close to the Planckian limit, the Hall angle varies as cot θ H ∝ T 2 and the low-field magnetores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Thus, the absence of enhanced T c near the nematic end point does not immediately rule out the important role of nematic fluctuations in this system. It has also been suggested that nematic fluctuations could be quenched by the strong coupling to the lattice or local strain effects in FeSe 1− x S x from quantum oscillation studies showing the absence of mass divergence near the nematic end point 27 , although the non-Fermi liquid behaviors are found in transport properties 28 , 29 . This situation calls for a different system to study the relationship between nematicity and superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the absence of enhanced T c near the nematic end point does not immediately rule out the important role of nematic fluctuations in this system. It has also been suggested that nematic fluctuations could be quenched by the strong coupling to the lattice or local strain effects in FeSe 1− x S x from quantum oscillation studies showing the absence of mass divergence near the nematic end point 27 , although the non-Fermi liquid behaviors are found in transport properties 28 , 29 . This situation calls for a different system to study the relationship between nematicity and superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, inside the nematic phase of FeSe 1−x S x , Kohler's rule is violated and the magnetoresistance of FeSe 1−x S x , follows an unusual B ∼1.55 power law in high magnetic fields [28]. Furthermore, scaling to a modified Kohler's rule as a function of the Hall angle was found in the vicinity of the nematic end point [123]. Another way to understand this complex behavior is to separate different components of magnetoresistance, as suggested in Ref.…”
Section: Magnetotransport Behaviour Of Fese 1−x S Xmentioning
confidence: 93%
“…Explaining these phase diagrams in detail, taking advantage of simultaneous transport and thermodynamic data, and using de Haas-van Alphen oscillation data to carefully account for the multi-band nature of many of these systems, is likely to provide strong constraints on theories of the underlying scattering. In this review we have not touched upon the rich phenomenology of magnetotransport [201][202][203][204][205][206][207][208] and low temperature thermal [209] and thermoelectric [210,211] transport that has also been demonstrated experimentally in Planckian systems. These will likely also provide fruitful hunting ground for future theories.…”
Section: Implications Of a Bound On Dissipationmentioning
confidence: 99%